Effective Rainfall in Haryana - Bishnoi, O P (Annals of Arid Zone, 2016)
The monthly and seasonal effective rainfall values have been estimated using monthly consumptive use, daily rainfall amounts, at various available soil moisture capacities of SO, 75,100 125, ISO mm within the root zone. Effective rainfall provides a useful guide to know the portion of rainfall which is ava-i1ablefor crop growth. During normal and. above normal. years of rainfall, the effective rainfall estimates vary considerably during the monsoon and post-monsoom season (July to October).